„Panienka”, „Godzina Polski”, 1916: Irena Tuwim’s Literary Debut - Kuczyńska-Koschany, Katarzyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The author of the article deals with the poetic newspaper debut of Irena Tuwim (1898-1987), an outstanding author and translator of children’s literature, but also a poet who is forgotten or read only on the margin of the literary output of her brother, Julian Tuwim (1894-1953). The poem titled Panienka (A Maiden), published in Godzina Polski in 1916, is hereby subjected to a contextual analysis and referred to other poems by Irena Tuwim as well as confronted with her existence, also in the auto-emancipatory dimension.